التحكيم وفقًا لاتفاقية الأمم المتحدة بشأن نقل البضائع عن طريق البحر (هامبورغ، 1978) - Ghassan, ali; Haidara, jaber (Tishreen University journal of research and scientific studies -economic and legal sciences, 2024)
International maritime transport represents the backbone of international trade in our current era, for many reasons, such as low costs and the ability to transport large quantities of goods at once. The United Nations Convention on the Maritime Transport of Goods of 1978, known as the Hamburg Convention, represents a qualitative shift in regulating the rules of maritime transport of goods. Among the important topics regulated by the agreement is the subject of arbitration, as it is the most important means of settling disputes related to international trade contracts, especially the contract for the maritime carriage of goods. Accordingly, this research studies the rules of the Hamburg Convention related to arbitration as a means of settling disputes related to the contract for the maritime carriage of goods. يمثل النقل البحري الدولي عصب التجارة الدولية في عصرنا الحالي، ألسباب عديدة كانخفاض التكاليف والقدرة عمى والمعروفة 1978 نقل كميات كبيرة من البضائع دفعة واحدة، وتمثل اتفاقية األمم المتحدة لمنقل البحري لمبضائع لعام ىامبورغ، نقمة نوعية عمى صعيد تنظيم قواعد النقل البحري لمبضائع، ومن بين الموضوعات اليامة التي باسم اتفاقية نظمتيا االتفاقية، موضوع التحكيم، باعتباره أىم وسائل تسوية النزاعات المرتبطة بعقود التجارة الدولية، وخاصة عقد د اتفاقية ىامبورغ المتعمقة بالتحكيم كوسيمة لتسوية النزاعات النقل البحري لمبضائع، وبناء عميو يتناول ىذا البحث قواع ال
Keywords: Arbitration; Bill of lading; Bills of lading; Carriage of Goods by Sea (1978); Hamburg Convention; Hamburg Rules; International commercial arbitration; Maritime carriage contract; Maritime transport; UN Convention; اتفاقية ىامبورغ; التحكيم; سند الشحن; عقد النقل البحري

الأعوان التجاريون لعملية النقل البحري - قزدعلي, أسماء (Université d'Oran 2 Mohamed Ben Ahmed, 2024)
الملخص : نظم القانون البحري الجزائري مهام و مسؤوليات كل من وكيل السفينة ووكيل الحمولة في المواد من 609 إلى 630 أما السمسار البحري فمن المادة 631 إلى المادة 639 ، فتعتبر هذه الأنشطة وليدة خوصصة النشاطات البحرية التي كانت محتكرة من قبل الدولة سابقا بالإضافة إلى ما أصبحت عليه السفن التجارية و تكاليفها الباهضة . كان ربان السفينة هو من يتولى القيام بهذه الأنشطة ذلك لحساب المجهز أو المرسل إليه ، فاقتضى الأمر إعفاءه منها ذلك نظرا لبقاء السفينة في الميناء مدة طويلة والبحث عن شخص طبيعي أو معنوي في كل ميناء يقوم لحساب المجهز أو المرسل إليه بتسليم البضائع وحراستها و المحافظة عليها و تحصيل الأجر عن ذلك . وعليه أصبح الأعوان التجاريون هم من يتولون القيام بهذه الأنشطة و المهام وذلك بناءا على عقد تنجر عنه جملة من الالتزامات و المسؤوليات على عاتق طرفاه . Le droit maritime algérien réglemente les fonctions et les responsabilités de consignataire du navire et de consignataire de cargaison dans les articles de 609 à 630. Le courtier naval de l’article 631 à l’article 639 considère ces activités comme la naissance de la privatisation des activités maritimes précédemment monopolisées par l’État en plus de ce que sont devenus les navires commerciaux et leurs coûts exorbitants. C’est le capitaine du navire qui a effectué ces activités au nom du transformateur ou du destinataire. Cela était rendu nécessaire par l’exemption, compte tenu du long séjour du navire au port et de la recherche d’une personne physique ou morale dans chaque port pour lequel le transformateur ou le destinataire livrait, gardait, entretenait et percevait les salaires. En conséquence, ce sont les agents commerciaux qui exercent ces activités et fonctions sur la base d’un contrat qui remplit un certain nombre d’obligations et de responsabilités des deux parties. Algerian maritime law regulates the duties and responsibilities of the ship’s agent and cargo agent in the section from 609 to 630. The naval broker from section 631 to section 639 considers these activities to be the birth of the privatization of maritime activities previously monopolized by the State in addition to what has become of commercial vessels and their exorbitant costs. The master of the vessel performed these activities on behalf of the processor or consignee. This was made necessary by the exemption, taking into account the vessel’s long stay in port and the search for a natural or legal person in each port for which the processor or consignee delivered, kept, maintained and collected wages. Consequently, it is the commercial agents who carry out these activities and functions on the basis of a contract which fulfils a number of obligations and responsibilities of both parties.
Keywords: Agency contract; Consignataire de cargaison; Consignataire de navire; Contrat de transport maritime; Contrat d’agence; Courtier maritime; Droit algérien; Droit maritime; Navire; Payload agent; Sea broker; Sea transport contract; Ship agent